Learning and adapting: the use of monitoring and evaluation in counter ing violent extremism: a handbook for practitioners - Dawson, Laura; Edwards, Charlie; Jeffray, Calum (Royal United Services Institute for Defence, 2014)
IN 2013, the Royal United Services Institute for Defence and Security Studies (RUSI) was awarded a grant under the Kanishka Project to devel op a handbook for monitoring and evaluating counter violent extremism (CVE) policies and programmes. The aim of this handbook is to support CVE policy-makers and practitioners (those who design, manage and eval uate CVE programmes), by providing them with key terms regarding viole nt extremism and radicalisation, describing the purpose of evaluation, and providing examples of key methodologies they can employ to conduc t monitoring and evaluation (M&E) in this emerging policy field. The h andbook will enable readers to understand why, when and how to conduct an evaluation of a CVE policy, programme or project. .